2014
DOI: 10.1155/2014/726861
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Induced Adipokine Changes and the Metabolic Syndrome

Abstract: The lack of adequate physical activity and obesity created a worldwide pandemic. Obesity is characterized by the deposition of adipose tissue in various parts of the body; it is now evident that adipose tissue also acts as an endocrine organ capable of secreting many cytokines that are though to be involved in the pathophysiology of obesity, insulin resistance, and metabolic syndrome. Adipokines, or adipose tissue-derived proteins, play a pivotal role in this scenario. Increased secretion of proinflammatory ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 157 publications
9
134
1
5
Order By: Relevance
“…Experimental evidence and anecdotal experiences suggest that stressed people consume more calories-condensed foods such as sweet and fatty foods and reduced amounts of micronutrients (129,249). This, coupled by the reduced rates of metabolism under conditions of stress (172), results in obesity and metabolic disturbances that can jeopardize the health of cardiovascular system in several ways (109,207). A recent report by Bergmann et al (27) that systematically analyzed prospective cohort studies scrutinizing the association between chronic psychological stress and the metabolic syndrome, concluded that psychological stress is a causal factor for development of the metabolic syndrome (27).…”
Section: Stress and Cardiovascular Adverse Effectsmentioning
confidence: 99%
“…Experimental evidence and anecdotal experiences suggest that stressed people consume more calories-condensed foods such as sweet and fatty foods and reduced amounts of micronutrients (129,249). This, coupled by the reduced rates of metabolism under conditions of stress (172), results in obesity and metabolic disturbances that can jeopardize the health of cardiovascular system in several ways (109,207). A recent report by Bergmann et al (27) that systematically analyzed prospective cohort studies scrutinizing the association between chronic psychological stress and the metabolic syndrome, concluded that psychological stress is a causal factor for development of the metabolic syndrome (27).…”
Section: Stress and Cardiovascular Adverse Effectsmentioning
confidence: 99%
“…Plenty of clinical study focused on the relationship between exercise and the plasma (or serum) adiponectin levels and the results are largely dependent on the duration and intensity of the exercise [83][84][85].…”
Section: Adiponectin In Exercisementioning
confidence: 99%
“…For the patients with obesity or diabetes, plenty of studies showed that the long-term training can decrease the level of TNF-α or/and IL-6 [83,[105][106][107][108], which demonstrate that the beneficial effects of exercise is partly mediated by decreasing the systemic inflammation.…”
Section: Inflammatory Adipokines Influenced By Exercisementioning
confidence: 99%
“…Mild to chronic exercise have shown to ameliorate both dyslipidemia and systemic inflammation [21]. Physical exercise might benefit obese partly through increased secretion of anti-inflammatory adipokines and decreased production of pro-inflammatory cytokines [22]. It has also been hypothesized that exercise promotes adipocyte oxidative capacity [23].…”
Section: Lessons From Pre-clinical and Clinical Researchmentioning
confidence: 99%